(untitled) (Ameghiniana, 2013)
Four species of charophytes are registred for the first time in the "Chubutense" beds (s. Feruglio). Two of them are Iorrns very closcly related to Flabellocbara barrisi (Peck) Grambast and Stellatocbara mundula Peck. The other two are assigned to the genus Mesochara Grambast and Peckisphaera Grambast. The age of the sediments with these charophytes is considered to be Lower Cretaceous.